Genome sequencing of rumen bacteria involved in lignocellulose digestion : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in the Institute of Molecular Biosciences at Massey University, Palmerston North, New Zealand - Palevich, Nikola; Palevich, Nikola (Massey University, 2011)
Determining the role of rumen microbes and their enzymes in plant polysaccharide breakdown is fundamental to understanding digestion and maximising productivity in ruminant animals. In order to learn more about lignocellulose degradation in pasture-grazed dairy cows under NZ conditions, twenty representative strains from five major phylotype clusters (Butyrivibrio fibrisolvens/hungatei cluster 383, Pseudobutyrivibrio xylanivorans clusters 247 and 245, Selenomonas ruminantium cluster 212, and Lachnospiraceae cluster 121), cultivated directly from the fibre-adherent rumen microbial fraction of dairy cows were selected. Genotypic and phenotypic analysis of these strains led to identification of Butyrivibrio sp. MB2003 that adheres to and efficiently degrades the plant fibre. The 3.3 Mb MB2003 genome was sequenced and annotated and found to consist of four replicons: a chromosome (7 contigs, in 1 super scaffold), a chromid (Bhu II), a megaplasmid (pNP144) and a small plasmid (pNP6). A novel feature of the MB2003 genome is the presence of a chromid (Bhu II) which is now the smallest chromid reported for all bacteria. The MB2003 polysaccharide-degrading enzymes, surface structures and predicted strategy for attachment to, and degradation of, complex polysaccharides was found to be comparable to that of the fibrolytic bacterium Butyrivibrio proteoclasticus B316. Both MB2003 and B316 are non-motile, despite the presence of flagellar gene clusters, and utilise a range of insoluble plant polysaccharides, but not cellulose. Xylan is the preferred insoluble substrate of MB2003 and its genome encodes a large repertoire of enzymes predicted to metabolise this complex polysaccharide. The MB2003 draft genome produced in this work is the first opportunity to conduct comparative analysis of two rumen bacteria belonging to the same genus. Although both MB2003 and B316 have similar phenotypic characteristics and occupy the same habitat, the genome of MB2003 is much smaller and contains fewer extracellular polysaccharide degrading enzymes. From this comparison it can be concluded that MB2003 is a secondary hemicellulose degrader, offering an alternate view of the genes required for a xylanolytic lifestyle in the rumen, and posing an interesting question about the purpose of the wider range of polysaccharide degrading enzymes found in B316.
Keywords: Rumen microbiology; Lignocellulose degradation; Bacterial genetics; Butyrivibrio